Hubungan Kadar Low Density Lipoprotein dengan Luaran Fungsional pada Stroke Iskemik - Hidayaturrahmi, Hidayaturrahmi; Imansyah Putra, Teuku Romi; Mizfaruddin, Muhammad; Dewi Mulia, Vera; Humaira, Dara; Al- Muchtari, T. Az Zikri (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: Stroke is the biggest cause of death and disability in the world. Ischemic stroke is the most common type of stroke caused by the formation of atherosclerosis in the brain. Abnormal levels of lipids in the body, especially low density lipoprotein (LDL), cause the formation of atherosclerotic plaques that also affect the functional outcome of ischemic stroke. Aim: The purpose of this study was to determine the relationship between LDL levels and the functional outcome of ischemic stroke at RSUDZA Banda Aceh. Methods: This research is a cross sectional study using purposive sampling which was analyzed by Fisher's test. Samples were 40 ischemic stroke patients in the RSUDZA neurosurgery ward who met the inclusion and exclusion criteria. Data were obtained from medical records to see LDL levels and interviews to assess the patient's functional outcome using the modified Rankin Scale score. Results: There were 32 patients with abnormal LDL levels and all of them had poor functional outcome (100%) with a p value of 0.000 (p<0.05). Discussion: The results of this study indicate that there is a significant relationship between LDL levels and the functional outcome of ischemic stroke in RSUDZA. Keywords: Ischaemic stroke, low density lipoprotein. functional outcome.